Cuantificación de la huella de carbono del desplazamiento de estudiantes a la facultad de agronomía-Zungarococha. Loreto 2022 - Salin Rojas, Jean Pierr (2022)
In the study, the carbon footprint of the mobile sources of the displacement to class of the students of the Faculty of Agronomy to the campus in Zungarococha, during the I semester of 2022, was determined. The methodology was based on the Corporate Accounting Standard, the Greenhouse Gas Protocol and emission factors of the IPCC (Intergovernmental Panel on Climate Change) and the Ministry of the Environment (MINAM). Direct emissions from the itinerary of the university buses (scope 1) and indirect emissions from private individual and mass transport (scope 3) were considered. A structured survey was applied to a sample of 396 students in order to obtain information on behavior when traveling to university. To calculate scope 1 emissions, a structured interview was conducted with those responsible for the university's transport units to determine the fuel consumption of the mobile units, and for scope 3 the average distance traveled by each type was determined. of transport used, which were converted to CO2e emissions the results of direct emissions from scope 1 due to Diesel fuel consumption reached 23.68 tCO2e, while total emissions from scope 3 are 111.86 tCO2e. Emissions for linear gasoline motorcycles are 94.72 tCO2e, for gasoline mototaxis 17.10 tCO2e and for Diesel B5 buses it is 0.04 CO2e. The total emissions of both Scope 1 with 23.68 tCO2e which represents 17.47 percent and those of Scope 3 with 111.86 tCO2e represents 82.53 percent. The contribution of undergraduate students to the total carbon footprint of 135.54 tCO2e and their per capita carbon contribution (| emissions) of the students of the Faculty of Agronomy is 0.17 tCO2e.